OCORRÊNCIA DE Scaptocoris castanea PERTY, 1839 (HEMIPTERA-HETEROPTERA, CYDNIDAE) EM Eucalyptus SP. (MYRTACEAE) - Berti Filho, Evoneo; Milani, Doraci; Cerignoni, João Angelo (REVISTA DE AGRICULTURA, 2015)
OCORRÊNCIA DE Scaptocoris castanea PERTY, 1839 (HEMIPTERA-HETEROPTERA, CYDNIDAE) EM Eucalyptus SP. (MYRTACEAE)